The Analysis of Protein-Bound Thiocyanate in Plasma of Smokers and Non-Smokers as a Marker of Cyanide Exposure - Youso, Stephanie L. (Oxford University Press, 2012)
When cyanide is introduced into the body, it quickly transforms through a variety of chemical reactions, normally involving sulfur donors, to form more stable chemical species. Depending on the nature of the sulfur donor, cyanide may be transformed into free thiocyanate, the major metabolite of cyanide transformation, 2-amino-2-thiazoline-4-carboxylic acid or protein-bound thiocyanate (PB-SCN) adducts. Because protein adducts are generally stable in biological systems, it has been suggested that PB-SCN may have distinct advantages as a marker of cyanide exposure. In this study, plasma was analyzed from 25 smokers (chronic low-level cyanide exposure group) and 25 non-smokers for PB-SCN. The amount of PB-SCN found in the plasma of smokers, 1.35 µM, was significantly elevated (p < 0.0001) when compared to non-smokers, 0.66 µM. Differences in sub-groups of smokers and non-smokers were also evaluated. The results of this study indicate the effectiveness of analyzing PB-SCN in determining instances of chronic cyanide exposure with possible extension to confirmation of acute cyanide exposure.